Alveolar ridge preservation using autogenous tooth graft versus beta-tricalcium phosphate alloplast: A randomized, controlled, prospective, clinical pilot study - Chaitanya Pradeep Joshi; Nitin Hemchandra Dani; Smita Uday Khedkar (Wolters Kluwer Medknow Publications, 2016)
Background: A randomized, prospective clinical, radiographical, and histological study was conducted to evaluate healing after alveolar ridge preservation technique using two different graft materials, namely, a novel autogenous graft material i. e., autogenous tooth graft (ATG) and beta-tricalcium phosphate (β-TCP) alloplast. Materials and Methods: Fifteen patients undergoing extraction of at least three teeth were selected. Atraumatic extractions were performed. Of the three extraction sockets, one was grafted with ATG, other with β-TCP, and the third was left ungrafted. Cone-beam computed tomography scans were taken immediately after grafting and 4 months postoperatively to check the changes in alveolar crest height and width at all the sites. Three patients in whom implant placement was done after complete healing; bone samples were harvested using a 3 mm diameter trephine during osteotomy preparation from both the ridge preserved sites and studied histologically. Results: There was a statistically significant difference when the changes in width and height of alveolar crest were compared within all the three groups (P < 0.05). Among three sites, ATG-grafted sites showed the most superior results with a minimal reduction in alveolar crest height and width. Histological analysis also showed the same trend with more new bone formation at ATG-grafted sites as compared to β-TCP-grafted sites. Conclusion: Postextraction, ridge preservation leads to more predictable maintenance of alveolar ridge height and width. ATG as compared to β-TCP provided superior results. Based on this, we conclude that ATG material can serve as a better alternative to conventional bone graft materials.